Collaborative quality improvement to promote evidence based surfactant for preterm infants: a cluster randomised trial. Issue 7473 (28th October 2004) - Horbar, Jeffrey D; Carpenter, Joseph H; Buzas, Jeffrey; Soll, Roger F; Suresh, Gautham; Bracken, Michael B; Leviton, Laura C; Plsek, Paul E; Sinclair, John C
Abstract: Objective To test a multifaceted collaborative quality improvement intervention designed to promote evidence based surfactant treatment for preterm infants of 23-29 weeks' gestation. Design Cluster randomised controlled trial Setting and participants 114 neonatal intensive care units (which treated 6039 infants of 23-29 weeks gestation born in 2001). Main outcome measures Process of care measures: proportion of infants receiving first surfactant in the delivery room, proportion receiving first surfactant more than two hours after birth, and median time from birth to first dose of surfactant. Clinical outcomes: death before discharge home, and pneumothorax. Intervention Multifaceted collaborative quality improvement advice including audit and feedback, evidence reviews, an interactive training workshop, and ongoing faculty support via conference calls and email. Results Compared with those in control hospitals, infants in intervention hospitals were more likely to receive surfactant in the delivery room (adjusted odds ratio 5.38 (95% confidence interval 2.84 to 10.20)), were less likely to receive the first dose more than two hours after birth (adjusted odds ratio 0.35 (0.24 to 0.53)), and received the first dose of surfactant sooner after birth (median of 21 minutes v 78 minutes, P < 0.001). The intervention effect on timing of surfactant was larger for infants born in the participating hospitals than for infants transferred to a participating hospital after birth. There were no significant differences in mortality or pneumothorax. Conclusion A multifaceted intervention including audit and feedback, evidence reviews, quality improvement training, and follow up support changed the behaviour of health professionals and promoted evidence based practice.